A solvent-free solid catalyst for the selective and color-indicating ambient-air removal of sulfur mustard - Daniel L. Collins-Wildman; Kevin P. Sullivan; Yurii V. Geletii; Victoria G. Snider; Wesley O. Gordon; Alex Balboa; Yiyao Tian; Rachel M. Slaugenhaupt; Alexey L. Kaledin; Christopher J. Karwacki; Anatoly I. Frenkel; Djamaladdin G. Musaev; et al. (Communications Chemistry, 2021)
Decontamination of sulfur-containing chemical warfare agents can be achieved through selective, air-based oxidation. Here a solid, solvent-free catalyst for aerobic oxidative decontamination of sulfur mustard is reported.